2012
DOI: 10.1055/s-0032-1321779
|View full text |Cite
|
Sign up to set email alerts
|

Kostenanalyse telemedizinischer Schlaganfallbehandlung

Abstract: Considering both health insurance and nursing care fund costs, the incremental costs for TeleStroke network care in hospitals are compensated by savings in outpatient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
1
6
0
1
Order By: Relevance
“…Patients treated at non-telestroke facilities had increased rates of ongoing care and institutionalization, requiring higher annual healthcare costs over the long term. Telestroke was cost neutral by 30 months, and for every year afterwards, cost effective by reducing lifelong costs of supportive care 20. Similar results have been replicated in other American and European contexts, demonstrating long term cost savings generated from improved functional outcomes and decreased hospital transfers 21–24.…”
Section: Expanding Access To Telestrokesupporting
confidence: 59%
See 1 more Smart Citation
“…Patients treated at non-telestroke facilities had increased rates of ongoing care and institutionalization, requiring higher annual healthcare costs over the long term. Telestroke was cost neutral by 30 months, and for every year afterwards, cost effective by reducing lifelong costs of supportive care 20. Similar results have been replicated in other American and European contexts, demonstrating long term cost savings generated from improved functional outcomes and decreased hospital transfers 21–24.…”
Section: Expanding Access To Telestrokesupporting
confidence: 59%
“…Coordinating these efforts requires an ongoing investment that, in the near term on an institutional level, can be more expensive than not treating AIS. The financial outlook of telestroke in a real world was recently assessed in a retrospective analysis of nearly 1300 AIS cases in a large German telestroke network 20. The cost of treatment was compared for patients treated in hospitals with or without telestroke capabilities and tracked for 30 months post-stroke.…”
Section: Expanding Access To Telestrokementioning
confidence: 99%
“…In 2002, health policy authorities decided to support telemedicine networks. When the controlled study showed that the TEMPiS concept was both improving clinical outcomes and cost effective when compared with conventional care (higher costs during acute care were fully compensated by lower rehabilitation and long-term care costs), 16 ongoing support by health insurances covering the teleconsultation service and the quality management program was decided in 2006. Meanwhile, the running costs of the TeleStroke Units for the regional hospitals are reimbursed within the German diagnosis related groups system.…”
Section: Discussionmentioning
confidence: 99%
“…a relative reduction by one fifth. The assumptions are based on the results of the TEMPiS trial [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of acute stroke using telemedicine resulted in more frequent and appropriate application of intravenous thrombolysis [ 10 , 11 ] and was associated with improved outcome [ 12 ]. What is more, “telestroke” proved to be cost-effective [ 13 ] making stroke one of the most frequent indications for telemedicine in several countries (Refs als from US, Germany etc).…”
Section: Introductionmentioning
confidence: 99%